The perspectives of metabolomics studies of potato plants - R. K. Puzanskiy; V. V. Yemelyanov; T. A. Gavrilenko; M. F. Shishova (Вавиловский журнал генетики и селекции)
According to FAO (Food and Agricultural Organization of the United Nation), potato is the fourth crop in terms of food production after rice, wheat and maize, and the first among the tubers and roots. The importance of potato is difficult to overestimate; it is a valuable source of carbohydrates, antioxidants and vitamins. A huge number of investigations are focused on the study of metabolic processes occurring in the potato plant in order to elucidate the mechanisms responsible for productivity and accumulation of compounds that determine taste and nutritional quality, keeping quality of tubers, plant resistance, etc. The sum of metabolites, which is produced as a result of metabolic network activity, is defined as metabolome. Complex studies of metabolic diversity with the use of modern state-of-the-art chromatography approaches and highly precise detection of individual compounds revealed specificity of metabolic spectra from subcellular to organism levels and its amazing plasticity under the influence of a variety of internal and external stimuli. Metabolomic approaches are already in use for phenotyping available species, lines and varieties as well as for evaluation of potato plant resistance to environmental challenges and for detection of changes in tubers during storage. Metabolome profiling is widely employed to study differences between genetically modified forms of potatoes from untransformed relatives. A limited number of systemic studies on potatoes combines metabolome investigation with genome, transcriptome and proteome analysis and suggests an important role of the genome in the determination of metabolic rates. It is obvious that the search for biochemical markers depends on standartization of cultivation techniques, sample preparation and subsequent analysis similar to what has been developed for progress in genomic and transcriptomic studies. In the future, potato metabolome studies might complete classical and molecular approaches to develop new lines and varieties.